Building brand and fan relationships through social media. Issue 3 (9th July 2018) - Thompson, Ashleigh-Jane; Martin, Andrew J.; Gee, Sarah; Geurin, Andrea N.
Abstract : Purpose: As the popularity of social media increases, sports brands must develop specific strategies to use them to enhance fan loyalty and build brand equity. The purpose of this paper is to explore how two social media platforms were utilised by the Grand Slam tennis events to achieve branding and relationship marketing goals. Design/methodology/approach: A content analytic design was employed to examine Twitter and Facebook posts from the official accounts during, and post-, each respective event. Findings: Both sites were utilised to cultivate long-term relationships with fans and develop brand loyalty, rather than to undertake short-term marketing activations. However, these sites appear to serve a different purpose, and therefore unique strategies are required to leverage opportunities afforded by each. Interestingly, brand associations were utilised more frequently during the post-event time period. Practical implications: This study offers practitioners with useful insight on branding and relationship-building strategies across two social platforms. These results suggest that strategies appear dependent on the event, timeframe and specific platform. Moreover, the events' differences in post use and focus may also indicate some differences related to event branding in an international context. Furthermore, sport organisations should look to leverage creative strategies to overcome limitations that platform-specific functionality may impose. Originality/value: This study offers unique insights brand-building efforts in an international event setting, which differ in a range of contextual factors that impact on social media utilisation.